Partisipasi Masyarakat Kelurahan sebagai Strategi Pemberdayaan dalam Pembangunan Berkelanjutan: Studi Kasus Kelurahan Ibuh dan Tigo Koto Diate, Kota Payakumbuh - Muhammad Surya Imam; Suci Rahmadini; Viona Gemila Netrius; Syahrunisya Salsabila Putri; Shania Dwi Brilliani; Raid Dzaki Yurian; Rizki Syafril (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
Community participation at the kelurahan (urban village) level in Indonesia remains low and largely induced, yet to reach the “citizen power” stage. This condition is caused by low literacy regarding formal participatory mechanisms (especially Musrenbang) and limited decision-making authority for citizens, thereby slowing the achievement of inclusive and sustainable development. This descriptive qualitative study aims to uncover the forms, characteristics, and effectiveness of community participation as an empowerment strategy in Kelurahan Ibuh and Kelurahan Tigo Koto Diate, Payakumbuh City, along with its contribution to the Sustainable Development Goals (SDGs). Data were collected through triangulation (observation, documentation, and in-depth interviews) involving the two kelurahan heads on 13 November 2025, and analysed in three stages: data reduction, data display, and conclusion drawing/verification. The findings reveal two distinct yet complementary participation patterns: (1) horizontal/bottom-up in Kelurahan Ibuh, driven by voluntary community awareness, and (2) vertical but highly enthusiastic in Kelurahan Tigo Koto Diate, mobilised through religious and customary activities. Both patterns effectively strengthen social cohesion, enable self-reliant maintenance of public facilities, and support SDGs Goal 11 (Sustainable Cities and Communities) and Goal 17 (Partnerships for the Goals). Nevertheless, participation remains induced and stays at the “tokenism” level due to low Musrenbang literacy and the dominance of decision-making by lurah (village heads) and customary leaders. Strengthening participatory literacy and expanding genuine citizen power are critical to accelerating inclusive and sustainable development at the urban village level.